Portugal : Staff Report for the 2000 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
Portugal showed impressive economic performance owing to its macroeconomic policies and structural reforms. Executive Directors commended the authorities for their stability-oriented policies, low inflation, and declining fiscal deficits. Nonetheless, economic policies needed to address signs of emerging macroeconomic imbalances, including the brisk growth of private sector credit, tight labor markets, and a persistent inflation differential in relation to other euro area countries. Moreover, an acceleration of structural reforms and further fiscal consolidation would be essential for a rapid and sustained convergence to European Union income levels.